Pengaruh Keterampilan Teknologi Terhadap Produktivitas Pada Subbagian Evaluasi dan Pengembangan SDM Dirjen Perhubungan Udara - Agus Tri Indah (Widya Cipta - Jurnal Sekretari dan Manajemen, 2017)
In this era of technology and civilization is very advanced, demanding human resources (HR) are competent and have high morale in the role and function both individually and organizationally. Technology skills are already high and increasingly sophisticated information technology will not result in work productivity when they can not be used regularly and seriousness. For that conducted this study aimed to investigate the influence of technology, especially information technology skills to work productivity of employees, especially civil servants. The study took place at the Division of Evaluation and Development of Human Resources Direktorat Jenderal Perhubungan Udara Jakarta. By taking the population in that section to be sampled by the sampling frame is based on education and class of thirty three employees. The research method uses quantitative methods and data obtained through the questionnaire, and extensive observation in the study supported with documents to strengthen the research results. The results showed that the technological skills has an effect on work productivity of civil servants and Evaluation Division of Human Resources Development Direktorat Jenderal Perhubungan Udara.